COAXIM, an innovative protocol for mass clonal propagation of coconuts: Merits of the technology, potency and progress - Panis, Bart; Wilms, Hannes (2025)
Indonesia Accelerates Coconut Tissue Culture Innovation with Bambu Nusa Verde, ICC, and BAPPENAS, Yogyakarta, Indonesia 10–11 October 2025